Understanding households' livelihood choices, wealth, and poverty in Accra, Ghana. Issue 3 (2nd April 2016) - Abraham, Ernest; Martin, Adrienne
ABSTRACT: This article reports on a study that aimed to deepen understanding of the factors which influence livelihood choices, and perceptions of wealth and poverty, in Accra, Ghana. Focus group discussions and household surveys were held in ten selected communities. Although parents are able to influence their households' livelihood choices, the prevailing socio-economic circumstances are more likely to determine what household members are likely to do. Perceptions of wealth and poverty are influenced by factors both internal and external to households, indicating the complexity and variety of interrelated assets which the poor depend on for their livelihoods.